Rorty and Kierkegaard on Irony and Moral Commitment - Frazier, B. author. aut Link
X, 249 p.
Keywords: This book seeks to clarify the concept of irony and its relation to moral commitment. Frazier provides a discussion of the contrasting accounts of Richard Rorty and Søren Kierkegaard. He argues that, while Rorty's position is much more defensible and thoughtful than his detractors acknowledge, it is surprisingly more parochial than Kierkegaard's.